PERLINDUNGAN HUKUM TERHADAP BANK SEBAGAI KREDITOR ATAS HAPUSNYA HAK ATAS TANAH OBYEK HAK TANGGUNGAN KARENA ADANYA KEGIATAN PENGADAAN TANAH - ARISANTA PEBRINA HELENA SIAMBATON (PREMISE LAW JURNAL, 2015)
The land rights regulated by the Law of the Republic of Indonesia No.5/1960 on Basic Regulation of Agrarian Principles holding the principle that all of the land rights have their social function. Therefore, the owner of the land rights have to release their land rights when the land acquisition activity is being implemented, no exception for the land rights being imposed with Collateral Right which guarantees to pay off certain debt to the bank. The problem appeared when the compensation were entrusted to the local District Court, the land rights were declared to be void, that the bank as the holder of the collateral lost special guarantee. The protection effort that can be taken by the bank is the inclusion of a clause granting power of attorney to the bank to withdraw the compensation money in the District Court related to the credit agreement mutually agreed by the debtor and the bank. Keywords: Legal Protection, Collateral, Land Acquisition